1998
DOI: 10.1046/j.1365-2141.1998.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and function of peripheral blood stem and progenitor cell harvests from patients with severe active rheumatoid arthritis

Abstract: High-dose chemotherapy with autologous stem cell rescue has been proposed as an intensive therapy for severe rheumatoid arthritis (RA). In view of previous observations of abnormal haemopoiesis in RA patients, the composition and function of peripheral blood stem cell harvests (PBSCH) was investigated. Compared with PBSCH from healthy allogeneic donors mobilized with the same dose of G-CSF (filgrastim; 10 microg/kg/d, n = 14), RA PBSCH (n = 9) contained significantly fewer mononuclear cells (375 v 569 x 10(6)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“…Progenitor cells have also been isolated from synovial fluid (34). Support for a reduction of the HPC pool in RA comes from studies describing reduced numbers of BM CD34ϩ cells and reduced recovery of CD34ϩ populations in RA patients undergoing BM transplantation (22,23). Finally, endothelial precursor cells are markedly reduced in RA patients, suggesting an age-inappropriate demise affecting several CD34ϩ subpopulations (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progenitor cells have also been isolated from synovial fluid (34). Support for a reduction of the HPC pool in RA comes from studies describing reduced numbers of BM CD34ϩ cells and reduced recovery of CD34ϩ populations in RA patients undergoing BM transplantation (22,23). Finally, endothelial precursor cells are markedly reduced in RA patients, suggesting an age-inappropriate demise affecting several CD34ϩ subpopulations (19).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in peripheral blood stem cell harvests, CD34ϩ cells were found to be reduced to 50% in RA patients as compared with healthy controls (22). Significantly lower percentages of CD34ϩ BM cells have been reported in RA patients who were candidates for autologous HSC transplantation (23).…”
mentioning
confidence: 99%
“…Outra estratégia para evitar recidivas, adotada no protocolo randomizado europeu (estudo ASTIRA) que usa CY+ATG no condicionamento, foi a introdução de imunossupressão em baixas doses (metotrexato 15 a 25mg/sem ou leflunomida) logo após a enxertia, como terapia de manutenção (10) . Entretanto, apenas um paciente foi transplantado até agora neste protocolo, pois a maioria dos pacientes com AR grave está participando de protocolos clínicos com agentes biológicos (anti-TNF, anti-IL-6, IL-1RA outros) (Bingham, comunicação pessoal (45) . Por outro lado, um estudo europeu com pacientes com AR candidatos a TCTH mostrou, ao lado de reduzido número de progenitores hematopoéticos na medula óssea dos pacientes, também uma redução da função hematopoética e aumento da apoptose nas células progenitoras mais primitivas.…”
Section: Artrite Reumatóide Do Adultounclassified
“…[18][19][20][21][32][33][34] Studies in other autoimmune diseases have already shown abnormalities in BM hematopoiesis [7][8][9][10] capable of affecting the mobilization and/or the engraftment of stem cells in patients undergoing ASCT. [11][12][13] In the current study, we have evaluated the reserves and functional characteristics of BM hematopoietic progenitor cells and the hematopoiesis supporting capacity of BM stromal cells in MS patients and we have found that these patients displayed normal proportion of CD34 þ hematopoietic progenitor cells in the BMMC fraction and normal proportion of early CD34 þ /CD38 À and committed CD34 þ /CD38 þ cells. In contrast, the clonogenic potential of hematopoietic progenitor cells was found to be significantly reduced in these patients as was demonstrated by the low CFC number obtained from BMMCs and purified CD34 þ cells in short-term BM cultures and the low CFC recovery in NACs from LTBMCs.…”
Section: Cytokines In Ltbmc Supernatantsmentioning
confidence: 99%
“…For example, it has been reported that patients with active rheumatoid arthritis and systemic lupus erythematosus display a low frequency of BM CD34 þ cells and impaired hematopoiesis supporting capacity of BM stromal cells due to the presence of autoreactive cells producing pro-inflammatory cytokines and proapoptotic mediators. [7][8][9][10][11] These abnormalities may give an explanation for the recently described difficulties or failures in the stem cell collection procedure 12 and occasional graft failure 13 in some patients undergoing ASCT. In contrast, patients with primary autoimmune cytopenias exhibit increased numbers of hematopoietic progenitor cells and normal BM stromal cell function in terms of its capacity to support hematopoiesis.…”
mentioning
confidence: 99%